2019
DOI: 10.9734/air/2019/v19i230116
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Entrepreneurship on the Sustainability of Selected Small and Medium Enterprises in Nigeria

Abstract: This paper examined the impact of social entrepreneurship on sustainability of business development in Nigeria. The objectives of the study include: to identify major evolution experienced by social enterprise in Nigeria, to identify key challenges in social entrepreneurship in Nigeria, to identify current trends in social entrepreneurship in Nigeria, and to carry out an analysis on sources of funds for financing the social entrepreneurs. Survey approach was the research design used with particular reference t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Therefore, the positive impact of Facebook adoption from their neighbouring competitors might be less obvious to them. It was also verified that government support was a significant and positive determinant of Facebook adoption (H6a), reinforcing the TOE framework and past studies (Ogbo et al, 2019). This result revealed that government assistance in the form of an enabling environment, training for SME owners and financial assistance would enhance Facebook adoption among service-based SMEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the positive impact of Facebook adoption from their neighbouring competitors might be less obvious to them. It was also verified that government support was a significant and positive determinant of Facebook adoption (H6a), reinforcing the TOE framework and past studies (Ogbo et al, 2019). This result revealed that government assistance in the form of an enabling environment, training for SME owners and financial assistance would enhance Facebook adoption among service-based SMEs.…”
Section: Discussionmentioning
confidence: 99%
“…Ogbo et al (2019) reported that government support was critical for promoting Facebook adoption among Nigerian SMEs. Moreover,Oni (2021) recently confirmed the positive influence of government support on Nigerian SME social media adoption.…”
mentioning
confidence: 99%
“…Despite the achievements and progress that accrue to an economy having a high concentration of social enterprises, some challenges still exist that can hamper the performance of these social enterprises. According to Ogbo et al (2019), it has been observed that technological factors, amongst others, are the significant evolution experienced by a social enterprise in Nigeria. Social entrepreneurs in Nigeria face other financial, administrative and economic conditions that withhold their full subscription to technology for process improvements (Matthew et al , 2020).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Social entrepreneurship is important because it can help increase growth, achieve a stable, fair, and prosperous economy, and become an innovative market in various countries (Acs et al, 2018;Aparicio, Urbano, & Gomez, 2018;Popov, Veretennikora, & Kozinskaya, 2018;Sohel, 2018, Ogbo et al, 2019Deng et al, 2020). Apart from creating high expectations, it is considered a new approach to tackling poverty and social exclusion in developing countries (Seelos & Mair, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%